INNOVATIVE ACTIVITIES LEGAL REGULATION IN AGRICULTURE IN THE EU - STOLIARCHUK, Nadiia; PIVTORAK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study aims to conduct a comprehensive analysis of the current state and structure of regulatory and legal frameworks governing innovative activity in the agricultural sector within the European Union. This research identifies the principal components of regulatory and legal mechanisms that influence innovation in EU agriculture, including the strategic and normative documents at the core of innovation policy. The research further examines the EU’s key legislative acts, strategic initiatives, and frameworks that shape innovation regulation in the agricultural domain, while outlining the principles and priority directions in policy implementation. Particular attention is given to the instruments of financial and institutional support that facilitate innovation processes, such as funding programs, research networks, public-private partnerships, and mechanisms for policy coordination. A significant section of the study is dedicated to the regulation of intellectual property (IP) in agriculture, covering topics such as patent protection for agricultural technologies, legal safeguards for plant varieties, trademarks and geographical indications, digital innovation in agriculture, and the protection of traditional knowledge and cultural practices in farming. The study highlights the most pressing challenges faced by EU member states in the implementation and enforcement of legal and regulatory measures. These include legislative fragmentation across national systems, lack of harmonization in legal instruments, regulatory obstacles to the adoption of emerging technologies, limited access to innovation financing for small and medium-sized enterprises, and insufficient legal incentives for cross-sector collaboration. In conclusion, the research outlines potential strategies and solutions aimed at improving the regulatory environment to foster innovation in agriculture, including enhanced policy integration, legal harmonization, and increased investment in capacity building and knowledge transfer mechanisms.